Parental burnout in Lebanon: Validation psychometric properties of the Lebanese Arabic version of the Parental Burnout Assessment. Issue 174 (14th December 2020) - Gannagé, Myrna; Besson, Eliane; Harfouche, Jacqueline; Roskam, Isabelle; Mikolajczak, Moïra
Abstract: This study‐ the first study on parental burnout in an Arabic speaking country in the Middle East‐ aimed to examine the psychometric properties of the Lebanese translation of the Parental Burnout Assessment (PBA‐Lebanese). The PBA‐Lebanese was administered to 200 Lebanese parents (67% mothers). The results showed parental burnout is a valid construct relevant to Lebanese culture. In particular, we replicated the original four‐factor structure of the PBA and we tested a second order factor structure through confirmatory factor analysis. The first and second order factor model fitted the data, and reliability indexes were high ( α = .97 for exhaustion, .95 for contrast, .92 for feelings of being fed up, .80 for emotional distancing and .98 for the global score). There was no significant gender difference in the prevalence of parental burnout, but mean levels were higher in mothers than in fathers. Both less educated parents and single parents reported higher parental burnout, pointing to the possible role of education and social relations as protective factors for Lebanese parents.